O RISO CÉTICO EM ADALGISA NERY E LOURENÇO MUTARELLI - MARCOS ANTONIO FERNANDES DOS SANTOS (2025)
This thesis investigates two novels from Brazilian literature, both of which were published over a thirty-year period (1972–2002). The novels in question are Neblina (1972), by Adalgisa Nery, and O cheiro do ralo (2002), by Lourenço Mutarelli. These works, while respecting the boundaries that separate them, address common themes and raise fundamental discussions about humanity, life, and even the power of the literary. The narratives are pervaded by doubt; skeptical thought serves as a structural core. Conversely, literary laughter, not always pleasant or funny, emanates from their reading. Skepticism and laughter were key issues of interest to us during the reading of these works. The research objective was, therefore, to demonstrate that different modes of narration, employed by two distinct Brazilian authors, work with gradations of laughter within dysphoric representations of the period between 1972 and 2002. For the construction of this research, we drew upon theorists such as Candido (1989; 2004), Dalcastagnè (1996), Pellegrini (1996), Minois (2003), Freud (1996), Bergson (1991), Bakhtin (2008), among others. The methodological approach was based on bibliographic procedures, a qualitative approach, and a critical reading of the literary texts. Despite each analyzed work possessing its own distinct characteristics, they converge in manifesting a skeptical and contemplative laughter when facing social, psychological, and existential realities permeated by repression, emptiness, disbelief, and hopelessness. In Adalgisa, the laughter is more contained; in Mutarelli, it is more aggressive. The latter’s skepticism is also more intense. Thus, these Brazilian novels elaborate distinct nuances of laughter through unique narrative forms.